PENGEMBANGAN PERANGKAT PERCOBAAN GEJALA HUKUM FARADAY SEBAGAI MEDIA PEMBELAJARAN FISIKA SMA - Diki Darmawan; Nur Islami; Yennita Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research aimed to produce an experiment's tools of Faraday symptoms expert and the valid student worksheet. So can be used as a learning media for senior highschool on material of electromagnetic induction. The used research methods are RESEARCH and DEVELOPMENT. In this research, the development of experiment's tools just till the validation step of the experiment's tools and student worksheet by several steps.The data was obtained from the validation of 3 lectuters and 2 teachers as validator. The validation was conducted in 2 phases, first phase was improvement and the second was assessment. The aspects which were assessed were the functionally of the equipment Very high category, the learning elements very high category, easiness very high category, esthetic and construction high category, and the safety Very high category. The aspect were assessed from student worksheet were the accuracy of content very high category, presentation prosperity high category, language prosperity high category, demonstration prosperity very high category Overall, each indicator of assessment in every aspect were declared as valid in very high category. In conclusion, faraday's legal trial was declared valid based. So it's feasible and valid to use as physics learning media for senior highschool on material of electromagnetic induction.Keywords : Experiment's equipment of Faraday Law,senior high school physics learning media